2013
DOI: 10.1186/1749-8090-8-164
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for the development of reexpansion pulmonary edema in patients with spontaneous pneumothorax

Abstract: BackgroundReexpansion pulmonary edema (REPE) is known as a rare and fatal complication after tube thoracostomy.ObjectivesWe investigated the risk factors for the development of REPE in patients with spontaneous pneumothorax.MethodsWe selected patients who were diagnosed with spontaneous pneumothorax and were initially treated with tube thoracostomy between August 1, 2003 and December 31, 2011. The patients’ electronic medical records, including operative notes and chest x-ray and computed tomography scans, wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 22 publications
1
24
0
1
Order By: Relevance
“…Because most cases are detected incidentally on radiography, the true incidence is still unclear (0.9 -20 %) [ 2 ]. The chest CT findings of reexpansion pulmonary edema are peripheral patchy lesions of ground glass opacity with a vascular distribution, which were usually associated with consolidation as well as interstitial thickening [ 2 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because most cases are detected incidentally on radiography, the true incidence is still unclear (0.9 -20 %) [ 2 ]. The chest CT findings of reexpansion pulmonary edema are peripheral patchy lesions of ground glass opacity with a vascular distribution, which were usually associated with consolidation as well as interstitial thickening [ 2 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Ͼ 30% of a collapsed lung field is another risk factor for RPE in patients with spontaneous pneumothorax, 3 and the incidence of RPE is higher when the collapsed lung is larger. 28 Because OLV was carried out in our 2 patients, almost 50% of the lung was collapsed. Thus, OLV itself may be a risk factor for RPE in patients who have preoperative lung injury and complications.…”
Section: Discussionmentioning
confidence: 99%
“…REPE was first reported in the mid‐1800s and is most commonly seen following large volume thoracentesis . Suggested risk factors for the development of REPE include; age between 20 and 40 years old, diabetes, duration of lung collapse, high negative pressures following drainage (more negative than ‐ 20 cmH2O), and draining greater than 1.5 L of fluid . Feller‐Kopman et al found in their retrospective review of 185 patients that REPE did not correlate with the amount of fluid withdrawn from the chest.…”
Section: Discussionmentioning
confidence: 99%